Dickkopf-3 As a New Potential Marker for Neoangiogenesis in Colorectal Cancer: Expression in Cancer Tissue and Adjacent Non-Cancerous Tissue. Issue 2 (2008) - Zitt, Matthias; Untergasser, Gerold; Amberger, Albert; Moser, Patrizia; Stadlmann, Sylvia; Zitt, Marion; Müller, Hannes M.; Mühlmann, Gilbert; Perathoner, Alexander; Margreiter, Raimund; Gunsilius, Eberhard; Öfner, Dietmar
Abstract : Gene expression of Dickkopf-3 (Dkk-3) has been shown to be upregulated in tumor endothelium of colorectal cancer (CRC). For the first time, we analyzed Dkk-3 protein expression in CRC and its potential as a marker for neoangiogenesis. We used tissue microarrays (TMAs) to investigate Dkk-3 in microvessels of 403 CRC samples, 318 appropriate adjacent non-cancerous samples and 127 normal colorectal samples. Of cancer samples with CD31-positive microvessels, 67.7% were positive for Dkk-3. Dkk-3 staining was demonstrated in endothelial cells of all microvessels in nearly all cases. Dkk-3-positive samples showed a higher mean microvessel count than did Dkk-3-negative samples ( P =0.001). Dkk-3 expression increased with rising numbers of microvessels per sample ( P <0.0001). In adjacent samples with CD31-positive microvessels, 56% were Dkk-3-positive in all microvessels. Similar to cancer samples, Dkk-3-positive adjacent samples had a higher mean microvessel count than did Dkk-3-negative samples ( P <0.0001), and Dkk-3 expression also increased with rising numbers of microvessels ( P <0.0001). All microvessels in normal mucosa samples were negative for Dkk-3. Dkk-3 can be considered a putative pro-angiogenic protein in neovascularization and may possibly be a marker for neoangiogenesis in CRC. Further investigations will elucidate whether Dkk-3 is a target structure for novel therapies.